Split groups in Sumenep: Inter-Islamic violence in 1998 - Isyqi, Mohammad Tibyan; Jauhari, Najib; Subekti, Arif (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
At the end of the New Order (Orde Baru) era, Indonesia was marked by inter-ethnic, inter-religious or religious violence. In Sumenep, Madura there was violence between groups that both claimed to be Sunni Muslims. Kiai Supardi, an immigrant who quickly rose to fame, initiated a group called Wali Songo Akbar in the early 1990s. In 1998, the Wali Songo Akbar Islamic Boarding School was vandalized and burned by a mob, then Kiai Supardi's followers demanded responsibility by kidnapping a local kiai which led to clashes. This paper aims to provide a description of the journey of the Wali Songo Akbar group that led to the violence that occurred in 1998. This article was written using the historical method by utilizing sources from newspapers, books, journal articles, and interviews. The Wali Songo Akbar group, better known as the tarekat, got the issue of heterodoxy that occurred, the issue marked repression and was ended by clashes that left 4 people dead, and several other Wali Songo Akbar followers lost their homes.